Successful extracorporeal membrane oxygenation for postoperative cardiopulmonary failure in newborns with congenital diaphragmatic hernia: case reports and literature reviews - Song-Ming Hong; Xiu-Hua Chen; Si-Jia Zhou; Jun-Jie Hong; Yi-Rong Zheng; Qiang Chen; Jin-Xi Huang (Frontiers Media S.A., 2023)
IntroductionCongenital diaphragmatic hernia (CDH) is a structural defect caused by inadequate fusion of the pleuroperitoneal membrane that forms the diaphragm, allowing peritoneal viscera to protrude into the pleural cavity. Up to 30% of newborns with CDH require extracorporeal membrane oxygenation (ECMO) support. As with all interventions, the risks and benefits of ECMO must be carefully considered in these patients. Cardiopulmonary function has been shown to worsen rather than improve after surgical CDH repair. Even after a detailed perioperative assessment, sudden cardiopulmonary failure after surgery is dangerous and requires timely and effective treatments.MethodThree cases of cardiopulmonary failure after surgical CDH treatment in newborns have been reported. ECMO support was needed for these three patients and was successfully discontinued. We report our treatment experience.ConclusionECMO is feasible for the treatment of postoperative cardiopulmonary failure in newborns with CDH.